Integrated transcriptomic and metabolomic analyses reveal the molecular mechanism of flower color differentiation in Orychophragmus violaceus - Shi, Yubin; Wang, Zixuan; Yan, Zhuangzhuang; Liu, Jianfeng; Zhang, Jun; Liu, Guixia (Frontiers in Plant Science, 2025)
IntroductionOrychophragmus violaceus is a popular horticultural plant because of its bright purple flowers that are commonly found in parks and green belts. However, three flower colors (purple, light purple, and white) were observed in the wild-type O. violaceus. The molecular mechanism underlying the formation of these intriguing flower colors remains unknown.MethodsHere, we combined metabolomics and transcriptomics to identify a pathway cascade leading to anthocyanin biosynthesis associated with flower color formation in O. violaceus.Results and discussionA total of 152 flavonoid metabolites were identified based on metabolomic data, most of which were quercetin and kaempferol. Comparative analysis of the metabolites among the three flower samples revealed that two anthocyanins, peonidin-3-glucoside and delphinidin 3-(6’’-malonyl-glucoside), are the pigments most likely responsible for the coloration of the petals of O. violaceus. Subsequent transcriptomic analysis revealed 5,918 differentially expressed genes among the three groups of flowers, 87 of which encoded 13 key enzymes in the anthocyanin biosynthetic pathway. Moreover, the high expression of two transcription factors, OvMYB and OvbHLH, in purple flowers suggests their role in the regulation of anthocyanin biosynthesis. By integrating metabolomic and transcriptomic data, OvANS, which encodes anthocyanidin synthase, was significantly upregulated in purple flowers. OvANS is the enzyme responsible for the transformation of colorless leucoanthocyanidins to colored anthocyanidins. This study provides novel insights into the molecular mechanism of flower color development in O. violaceus, laying the foundation for flower color breeding.